2011
DOI: 10.1002/joc.2147
|View full text |Cite
|
Sign up to set email alerts
|

The South American Monsoon System and the 1970s climate transition

Abstract: ABSTRACT:The South American Monsoon System (SAMS) is characterised by intense convective activity and precipitation during austral summer. This study investigates changes in the onset, demise and duration of SAMS during 1948SAMS during -2008. The results show a significant change in these characteristics in the early 1970s. Onset becomes steadily earlier from 1948 to early 1970s and has occurred earlier than 23-27 October after 1972-1973. Demise dates have remained later than 21-25 April after the mid-to-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 54 publications
3
77
1
8
Order By: Relevance
“…Previous papers have all documented an increase in the moisture flux over TSAM after the mid-1970s (Curtis and Hastenrath 1999;Marengo 2004;Carvalho et al 2011).…”
Section: Vimf and Divergence Of Vimfmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous papers have all documented an increase in the moisture flux over TSAM after the mid-1970s (Curtis and Hastenrath 1999;Marengo 2004;Carvalho et al 2011).…”
Section: Vimf and Divergence Of Vimfmentioning
confidence: 97%
“…Still, regarding multidecadal SAMS variability, Carvalho et al (2011) found an earlier onset and a delayed demise (i.e., an overall increase in duration) of the SAMS rainy season from the beginning of the 1970s. The same authors also argued that a rise in the vertically integrated moisture flux over TSAM favored the observed precipitation increase over the southern Amazon andCentral Brazil after 1971-1972. Analyzing rainfall over the Amazon for the 1929-1998 period, Marengo (2004) discovered shifts in rainfall regimes in both northern and southern sub-basins in 1946-1947and 1976-1977, consistent with PDO climatic shifts.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The austral winter corresponds to the dry season in most of the region, although it represents a rainy maximum for the far northwest of the basin. Well-defined wet and dry seasons are associated with the so-called South American Monsoon System, hereafter SAMS (Carvalho et al, 2011). Within the SAMS, the South Atlantic Convergence Zone (SACZ) represents a dominant feature of the wet season and is seen as a wide region of rainfall extending from the northwest to the southeast of the Basin and reaching the southern Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated regional anomalies of atmospheric circulation , the effects of low-level circulation (Nogués- Paegle & Mo 1997, Salio et al 2002, Liebmann et al 2004, Silva et al 2009), the effects of soil conditions in regions close to SESA (Grimm 2003, Grimm et al 2007, Grimm & Zilli 2009, changes in the onset and duration of the monsoon season during long-term periods (Carvalho et al 2011), and the influence of SST anomalies in oceans other than the Pacific.…”
Section: Introductionmentioning
confidence: 99%